The psychological contributions of pragmatism and of Original Institutional Economics and their implications for policy action - Arturo Hermann (Economic Thought, 2020)
The aim of this work is to illustrate the psychological contributions of Pragmatism and of the Original Institutional Economics (also referred to as OIE or institutionalism), and their relevance for improving the process of social valuing and, as a consequence, the effectiveness of policy action. As a matter of fact, both institutionalist and pragmatist theories were well acquainted with various strands of psychology, and some of them also provided relevant contributions in this respect. Moreover, these theories reveal, along with various differences, significant complementarities, both between themselves and with important concepts of social psychology and psychoanalysis. The work will address the following aspects: (I) The main characteristics of pragmatist psychology with particular attention to their social implications. For space reasons, we will focus attention on the contributions of authors - John Dewey, William James and George Herbert Mead - more oriented to social sciences. (II) The psychological contributions of institutionalism. We will pay particular attention to Thorstein Veblen's theory of instincts and John Rogers Commons' theory of negotiational psychology. We highlight that these theories present, despite a number of differences, relevant complementarities. (III) The implications of the previous analysis for improving the process of policy formulation. We will address some aspects of the intertwined issues of social valuing and democratic planning. For instance, in devising policies for promoting workers' motivations, the focus will be not only on the monetary side but also on the adoption of measures aimed at promoting participation in the management of their institutions.
Keywords: 330; institutionalism; pragmatism; social valuing; interdisciplinarity; policy action